Impact of the Level of Maternal Education on Maternal and Newborn Health in Nigeria (2022)
Cross-sectional studies have shown a number of factors Chat impact maternal health, including socioeconomic status, health-seeking behaviours, and education. The objective of this study was to establish the impact of maternal education on maternal and newborn health in Nigeria. The design adopted for this study was retrospective. The 2018 NDHS and global data were used as primary sources for the study. Predictive factors responsible for good health indicators were considered for all the States in Nigeria. The educational status of the mother and utilization of maternal and newborn health Services were considered for analysis. The result showed a strong link between maternal education and maternal health in Nigeria, just as it exists in other parts of the world. It was concluded that maternal education knits many social parts together and creates a whole piece of interaction, creating a better health outcome. Literate women were more likely to deliver in health care facilities under the supervision of skilled birth attendants. They are also more likely to present themselves and their newborns for postnatal care. The benefits of maternal education extend beyond just the direct recipients of the education; children also benefit from maternal schooling as maternal education significantly reduces the risk of not accessing maternal and newborn health Services. Therefore, more attention should be given to girl-child education as a strong social determinant of health when devising strategies to reduce maternal mortality and to achieve universal health coverage in Safe Motherhood.